2016
DOI: 10.2174/1573399811666150812142922
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Diabetes Mellitus and Exposure to the Environmental Toxicant Cadmium with an Emphasis on Likely Mechanisms of Action

Abstract: There is increasing interest in how exposure to environmental substances can contribute to the onset of Type II diabetes mellitus (T2DM). Impaired insulin release is a hallmark of type I diabetes mellitus and is involved in the progression of T2DM. Both epidemiological and experimental studies show that exposure to the environmental pollutant cadmium (Cd), is associated with hyperglycemia, T2DM and reduced serum insulin. The goal of this review is to examine likely mechanisms of action of Cd-induced dysglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 56 publications
0
52
0
Order By: Relevance
“…Similarly, several studies conducted in various populations including United States, 15 Korea 16 and China, 17 suggest that a direct correlation exists between Cd exposure and risk of DM. Numerous studies have revealed that Cd‐induced hyperglycaemia resulted in enhanced lipid peroxidation, reduced insulin secretion, enhanced activity of gluconeogenic enzymes and impaired insulin receptor signalling 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies conducted in various populations including United States, 15 Korea 16 and China, 17 suggest that a direct correlation exists between Cd exposure and risk of DM. Numerous studies have revealed that Cd‐induced hyperglycaemia resulted in enhanced lipid peroxidation, reduced insulin secretion, enhanced activity of gluconeogenic enzymes and impaired insulin receptor signalling 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Diet and tobacco smoking are the primary sources of human exposure to cadmium (WHO, 2010b), which then accumulates in the body, as it has a half-time of over of 26 years (ATSDR, 2012). The deleterious effects include carcinogenicity (IARC, 2012), end-stage renal failure (Kobayashi et al, 2008), bone demineralisation, (Kjellstr € om, 1992), reproductive and developmental toxicity (Gupta, 2011) and disturbance of metabolism (Edward and Ackerman, 2016) and macro-and micronutrients homeostasis (Kim et al, 2007).…”
Section: Case Study 1 Risk Assessment On Cadmium In Foodmentioning
confidence: 99%
“…Concerning environmental and/or occupational exposure in the pathogeny of diabetes, several studies incriminated persistent organic pollutants (polychlorinated biphenyls, organochlorine pesticides, polyciclic aromatic hydrocarbons, phthalates etc) [6], metals (arsenic, cadmium) [7]. Therefore, with proper technical masures, all employees should avoid occupational contact with these substances.…”
Section: The Contribution Of Environmental Exposure To Type 2 Diabetementioning
confidence: 99%
“…Exposure to persistent organic pollutants (polychlorinated biphenyls, organochlorine pesticides, polycyclic aromatic hydrocarbons, phthalates etc) [6], heavy metals (arsenic, cadmium) [7] need to be avoided as they have a potential role in the pathogeny of diabetes. With correct technical measures, all employees should avoid occupational contact with these substances, not only by those already diagnosed with T2D.…”
Section: Type 2 Diabetes With Chronic Kidney Disease Evaluation In Ocmentioning
confidence: 99%